Integración de tecnología y pedagogía en la Biblioteca Infantil “Miriam Álvarez Brenes” de la Universidad Nacional - Miranda Campos, Guiselle (2013)
The time has now come to demand something very different in the various libraries of the UNA. "Learning to live, learning to learn" is a way of acquiring new knowledge over a lifetime, learning to think freely and critically, learning to love the world and make it more human and learning to be fulfilled through work, is the idea that led to reflect on the important role that libraries play in the learning process. In this context, it should be emphasized that technology is essential for the literacy of the library user population and that library professionals as mediators between information and users should prepare responsibly and enjoy these changes and possibilities. This research work is based on the implementation of a methodology that aims to enable users to access information and knowledge in a more agile, friendly and interactive way in ICT-enriched learning environments. This methodology has been designed for a children's library, but due to its applicability it can be used in any type of library, both inside and outside the National University.